“Kemoq” as A Traditional Method of Sasak People Explaining and Interpreting Literary Texts - Nuriadi Nuriadi (Budapest International Research and Critics University, 2022)
This article examines how the application of 'kemoq' as a method of explanation andinterpretation in literary discourses/texts in the Sasak ethnic group and looks at its position in relation to the concepts of literary criticism that have developed in modern literature. Sasak are ethnic groups or tribes that inhabit the island of Lombok, NTB. Most of the Sasak people are Muslim, so Islamist culture is quite visible in the literary texts that developed in the area. These texts play a fairly central role in the process of spreading religious teachings in the area and usually the parties who carry out the transformation process are community leaders who are recognized as having broad abilities and understanding of religion and the concept of life in general. These community leaders have been present and played a role before the presence of the teachers who currently play a very central and dominant role. the texts, which were read in the Mewacan (Mocopatan) program, are still written on palm leaves with the inscription Jejawan. To understand it, these figures usually apply the Kemoq method. This method is closely related to the play of words and sounds as long as it has a meaning that is more or less supportive of the initial concept of the interpreter, so that the meaning is very subjective, relative, and situational. However, with the application of this method the text message will develop and be easily understood by the audience.